PRIVATE SECTOR PARTICIPATION IN THE GREEN ECONOMY: A LITERATURE REVIEW ON BUSINESS SUSTAINABILITY - Lucky Mahesa Yahya; Al-Amin (Adisam Publisher, 2025)
The green economy has become an increasingly important global issue in the last decade, with the private sector playing an increasingly significant role. This research aims to examine the impact of private sector participation in the green economy on business sustainability. Through a literature review, this study analyses how green practices adopted by companies can benefit operational sustainability, reputation, resilience, innovation, and the development of a sustainable business ecosystem. The results show that private sector participation in the green economy can improve operational efficiency, strengthen corporate reputation and attractiveness, and encourage innovation and development of more environmentally friendly products. In addition, collaboration with other stakeholders can also shape a more sustainable business ecosystem. Thus, private sector involvement in the green economy not only has a positive impact on the environment, but can also support business sustainability in the long run.